Netter atlas of human anatomy : classic regional approach - Netter, Frank H. (Frank Henry), 1906-1991; Machado, Carlos A. G.; Neumann, Paul E.; Tubbs, R. Shane; Benninger, Brion; Hoagland, Todd M.; Gdowski, Martha J; Brueckner, Jennifer K., 1970-; Lyons, Virginia Taylor; Ward, Peter J.; Hansen, John T. (Philadelphia, PA : Elsevier, 2023)
"For students and clinical professionals who are learning anatomy, participating in a disSectionion lab, sharing anatomy knowledge with patients, or refreshing their anatomy knowledge, the Netter Atlas of Human Anatomy illustrates the body, region by region, in clear, brilliant detail from a clinician's perspective. Unique among anatomy atlases, it contains illustrations that emphasize anatomic relationships that are most important to the clinician in training and practice. Illustrated by clinicians, for clinicians, it contains more than 550 exquisite plates plus dozens of carefully selected radiologic images for common views"--Publisher's website
Section 1: Introduction -- General anatomy -- Systematic anatomy -- Electronic bonus plates Section. 2: Head and neck -- Surface anatomy -- Bones and joints -- Neck -- Nose -- Mouth -- Pharynx -- Larynx and endocrine glands -- Eye -- Ear -- Brain and meninges -- Cranial and cervical nerves -- Cerebral vasculature -- Regional imaging -- Structures with high clinical significance -- Cranial nerves -- Branches of cervical plexus -- Muscles -- Electronic bonus plates -- Section. 3: Back -- Surface anatomy -- Vertebral column -- Spinal cord -- Muscles and nerves -- Cross-Sectionional anatomy -- Structures with high clinical significance -- Muscles -- Electronic bonus plates -- Section. 4: Thorax -- Surface anatomy -- Thoracic skeleton -- Mammary glands -- Thoracic walls and diaphragm -- Lungs, trachea, and bronchi -- Heart -- Mediastinum -- Cross-Sectionional anatomy -- Structures with high clinical significance -- Muscles -- Electronic bonus plates -- Section. 5: Abdomen -- Surface anatomy -- Abdominal wall -- Peritoneal cavity -- Stomach and intestines -- Liver, gallbladder, pancreas, and spleen -- Visceral vasculature -- Visceral nerves and plexuses -- Kidneys and suprarenal glands -- Lymphatics -- Regional imaging -- Cross-Sectionional anatomy -- Structures with high clinical significance -- Muscles -- Electronic bonus plates -- Section. 6: Pelvis -- Surface anatomy -- Bony pelvis -- Pelvic diaphragm and viscera -- Urinary bladder -- Female internal genitalia -- Female perineum and external genitalia -- Male perineum and external genitalia -- Homologies of male and female genitalia -- Male internal genitalia -- Rectum and anal canal -- Vasculature -- Nerves of perineum and pelvic viscera -- Cross-Sectionional anatomy -- Structures with high clinical significance -- Muscles -- Electronic bonus plates -- Section. 7: Upper limb -- Surface anatomy -- Shoulder and axilla -- Arm -- Elbow and forearm -- Wrist and hand -- Nerves and vasculature -- Regional imaging -- Structures with high clinical significance -- Nerves of brachial plexus -- Muscles -- Electronic bonus plates -- Section. 8: Lower limb -- Surface anatomy -- Hip, buttock, and thigh -- Knee -- Leg -- Ankle and foot -- Nerves -- Regional imaging -- Structures with high clinical significance -- Nerves of lumbosacral plexus -- Muscles -- Electronic bonus plates. -- References -- Index
Includes bibliographical references and index
Keywords: Human anatomy -- Atlases.http://id.loc.gov/authorities/subjects/sh85004840; Anatomy.http://id.nlm.nih.gov/mesh/D000715.https://id.nlm.nih.gov/mesh/D000715; Humans.http://id.nlm.nih.gov/mesh/D006801.https://id.nlm.nih.gov/mesh/D006801; Atlas.http://id.nlm.nih.gov/mesh/D020466.https://id.nlm.nih.gov/mesh/D020466